The use of antidepressants in oncology: a review and practical tips for oncologists. (9th October 2017) - Grassi, L; Nanni, M G; Rodin, G; Li, M; Caruso, R
Abstract: Background: The use of psychotropic drugs, namely those with an antidepressant profile (ADs), is a mandatory part of an integrated treatment of psychiatric disorders among cancer patients. We aimed to synthetize the most relevant data emerging from published studies to provide tips about the use of ADs in oncology. Design: A search was made of the major databases over the last 30 years (Embase/Medline, PsycLIT, PsycINFO, the Cochrane Library), including narrative reviews, systematic reviews and meta-analyses summarizing the results from observational studies and randomized clinical trials assessing effectiveness, safety profile, interactions, contraindications and use of ADs in oncology with regard to both psychiatric (depressive spectrum, stress-related, anxiety disorders) and cancer-related symptoms (e.g. pain, hot flashes and fatigue). Results: The weight of evidence supports the efﬁcacy of ADs for more severe major depression in individuals with cancer and as an adjuvant treatment in cancer-related symptoms, although the methodological limitations of reported randomized controlled trials do not permit definite conclusions. Data also indicate that there should be caution in the use of ADs in cancer patients in terms of their safety profile and potential clinically significant interactions with other prescribed medications. Practical recommendations that have been made for the use of ADs in cancer patients, in the context of a multimodal approach to depression treatment, have been summarized here. Conclusions: ADs are a relatively safe and effective treatment for more severe major depression in cancer patients. However, more research is urgently needed regarding the efficacy of ADs in different cancer types and cancer settings, their interactions with anticancer agents and their additive benefit when integrated with psychosocial interventions.